(untitled) (Third Sector Social Economic Review, 2026)
Social expenditure stands out as one of the key policy instruments promoting inclusive and sustainable economic growth. In many developing countries, the public sector plays a leading role in providing services such as education, health, and social protection, which are vital to human capital formation and development. In this context, it is crucial to determine whether public social expenditure contributes to long-term economic growth in Türkiye, a developing country. In this context, this study analyzes the influence of social expenditures on economic growth in Türkiye for the period 1980–2024, using Fourier-based econometric methods (Fourier KPSS, Fourier-Shin, and Fourier-DOLS). Findings from the Fourier-Shin method indicate that public social expenditures and economic growth are cointegrated in the presence of structural breaks. Long-term coefficients calculated using the Fourier-DOLS method imply that public social expenditures have a positive and statistically significant effect on economic growth. Such a finding highlights the importance of public social expenditures for inclusive and stable long-term economic growth in Türkiye, consistent with the predictions of endogenous growth models. Policymakers should allocate additional resources to social expenditures and take measures to improve their quality to ensure inclusive and stable economic growth over the long term.